THE EFFECT OF SUPERVISION ON EMPLOYEE WORK DISCIPLINE THROUGH ORGANIZATIONAL CULTURE AS AN INTERVENING VARIABLE ON EMPLOYEES OF PT. LUTHFI ARYA TEKHNIK FROM AN ISLAMIC ECONOMIC PERSPECTIVE - Tri Wulandari; Erike Anggraini; Anas Malik (Nurul Jadid University, 2025)
This study aims to analyze the influence of supervision on employee work discipline through organizational culture as an intervening variable at PT. Luthfi Arya Tekhnik from an Islamic economic perspective. Human resources are strategic assets in the construction industry that require an effective supervision system and a strong organizational culture to achieve optimal levels of work discipline. The integration of Islamic economic values such as amanah, muraqabah, and ihsan provides a spiritual dimension that can strengthen the relationship between supervision and employee work discipline. The study used a quantitative approach with an explanatory survey design on 136 employee respondents selected through stratified proportional random sampling. Data were collected using a structured questionnaire with a Likert scale and analyzed using path analysis techniques. The results showed that supervision had a positive and significant effect on work discipline with a path coefficient of 0.762 (p<0.05). Supervision also had a significant effect on organizational culture with a coefficient of 0.789, while organizational culture had an effect on work discipline with a coefficient of 0.432. The Sobel test confirmed that organizational culture acts as a significant mediator (z=4.273, p<0.05) with a mediation effect of 44.7% of the total influence of supervision on work discipline. The findings indicate that the implementation of Islamic economic values in the supervision system and organizational culture is effective in improving employee work discipline through the development of spiritual awareness and trustworthy responsibilities. This study provides theoretical contributions to the development of Islamic management theory and practical implications for human resource management in the Indonesian construction industry.